FACTORS AFFECTING IMPLEMENTATION E-GOVERNMENT IN THE GOVERNMENT OF WEST SUMATRA PROVINCE (Study on West Sumatra Provincial Government Employees) - Eko Kurniawan Eko; Vera Pujani; Hendra Lukito (Management Department, Faculty of Economics and Business, Universitas Jambi, 2022)
This study aims to determine the factors that influence the implementation of E-Government in the Government of West Sumatra Province. The number of samples taken as many as 100 respondents. Based on the results of the validity test, it can be seen that all statements used to measure the E-Government variable are declared valid, because each statement has a corrected item total correlation coefficient above 0.65. While the reliability test with internal consistency test has a composite reliability value that meets the criteria. Based on the test results, all variable indicator statements have met the criteria of validity and reliability. The results of hypothesis testing using SPSS for windows version 23.0 with t-test analysis or t-test indicate that the quality of Human Resources and Communication has a positive and significant effect on the implementation of E-Government in the government of West Sumatra Province. Meanwhile, Infrastructure and Leadership have no significant effect on the implementation of E-Government in the West Sumatra Provincial government.